Saff Suresi’ nin din eğitimi açısından yorumu - Kurtuluş, Kıymet (My University, 2000)
An Interpretation of the Chapter Saff from the Perspective of Religious Education Every educational system has a philosophical ground on which it is built. For Islamic educational system, Qur'an is the philosophical ground. Guided with this idea, I have studied the Chapter Saff from the perspective of the Religious Education. I attempted to interpret this chapter aiming at attaining guiding principles in Religious Education. I have examined the Chapter Saff dividing it into five parts. In the first chapter of the thesis, Tesbih Ibadeti, I have dealt with the concept of 'tasbih,' human act of 'tasbih' as a kind of worship, and the relationship between 'tasbih' and education. I have discussed the implications of the concept 'tasbih' for education. In the second chapter, entitled Soz ve Davranis Butunlugu, I have tried to articulate the principle, 'the agreement between words and behaviors' could mean by examining examples from the life of the Prophet peace be upon, relationships within family members, between student and teacher. I have also looked at how this principle might be observed in politics with regard to the relationship between politicians and people. In the third chapter, Spiritual Trade I explained the spiritual trade according to the Qur'an, looking from the perspective that the Chapter Saff presents. I tried to answer questions regarding the nature of spiritual trade, which deeds are considered within the spiritual trade, and the function of the spiritual trade. The fourth chapter, Zulum, comprises discussions about the concepts that are related to 'injustice,' such as 'shirk,' 'inkar' and 'fisk,' and the behaviors related to these concepts. The fifth chapter explores the harmful behaviors that were committed by Jews. It also includes discussions regarding the prediction of the prophethood of Muhammad, peace be upon, by Jesus and Moses. In the Conclusion part, I summarized my conclusions and made some comments. SAFF SURESİ'NİN DİN EĞİTİMİ AÇISINDAN YORUMU Her eğitim sisteminin temelinde bir eğitim felsefesi vardır. Kur'an da İslam eğitim sisteminin temelini oluşturmaktadır. Biz de bu düşünceden yola çıkarak araştırmamızda Kur'an-ı Kerim'in bir suresi olan Saff suresi çerçevesinde Kur'anla eğitim bilimleri konularını biraraya getirdik. Bu sureyi eğitim açısından değerlendirmeye çalışarak, eğitimle ilgili çıkarımlar yapmayı amaçladık. Saff suresinde beş bölüm tespit edilmiştir. Birinci bölümde,Tesbih İbadeti başlığı altında, tesbih kavramı, insanın Allah'ı ibadet şeklindeki tesbihi ve sonunda da tesbih ve eğitim konularından bahsedilerek eğitimle ilgili değerlendirmeler yapılmıştır. Söz ve Davranış Bütünlüğü adı altındaki ikinci bölümde ise sırasıyla Hz.Peygamber (S.A.V)'in hayatından davranış modelleri, aile, öğretmen ve öğrenci, siyaset ve halk ilişkileri konuları ele alınarak insanın içi ile dışının, özü ile sözünün çelişik olmaması gerektiği eğitim yönünden incelenmiştir Manevi Ticaret başlığı taşıyan üçüncü bölümde ise Saff suresi perspektifinden bakarak, Kur'an-ı Kerim'e göre manevi ticaret, hangi ameller manevi ticaret olur ve manevi ticaretin işlevi ile ilgili konular ele alınmıştır. Dördüncü bölümde ise Zulüm başlığı adı altında zulme yakın kavramlardan şirk, inkâr, fâsık ve zulüm olarak nitelendirilen davranışlar konu edinilmiştir. Beşinci bölümde Hz. Musa ve Hz.İsa'ya İsrailoğulları'nın yaptıkları eziyetlerden bahsedilmiş, ayrıca Hz.İsa'nın Hz.Muhammed (S.A.V)'i müjdelemesi konuları ele alınmıştır. Sonuç bölümünde ise elde edilen bulgular çerçevesinde araştırma özetlenerek yorum ve değerlendirmeler yapılmıştır.
Keywords: Ayetler ve sureler (Kuran); Din eğitimi